Primary tubulovillous adenoma of the urinary bladder: Case report and literature review - I-Hsuan Chen (Urological Science, 2014)
Primary tubulovillous adenomas are scarcely encountered in the urinary tract, and most of these tumors arise from the intestinal segments of urinary reconstruction. We report the extremely rare case of tubulovillous adenomas primarily occurring in the urinary bladder in this article. A 50-year-old female patient initially presented with painless gross hematuria for several times within 1 month. Image studies, including abdominal ultrasonography and computed tomography, demonstrated one urinary bladder tumor with suspicious perivesical invasion. The diagnosis was made by a transurethral resection and histopathology, and no involvement of muscularis propria was confirmed. Although the pathogenesis and clinical behavior are not well understood, tubulovillous adenomas may have a tendency to undergo malignant transformation into the form of invasive adenocarcinomas. Complete resection and rigorous follow-up are strongly recommended.